Chinese Ancient Coin - Uang kepeng: A Strengthener of Bali and China Relationship - RAKA, Anak Agung Gede; MARDIKA, I Made; WAHYUNI, Ni Made; WARMADEWI, Anak Agung Istri Manik (Journal of Environmental Management and Tourism, 2020)
Relations between Bali and China have been established since the Han Dynasty around 100 BC. This opinion was strengthened by the discovery of nekara, a bronze kettle drum, in Pejeng, Gianyar. The relationship between Bali and China is a trade relation in which Bali was written in the notes of Chinese traders who came to Southeast Asia in the 5 th century. One of the legacies of Chinese trade in Bali is the uang kepeng (ancient Chinese coin) which was used as a means of a transaction at that time. The existence of uang kepeng in Bali is very interesting to discuss because of the transformation of its function. Previously uang kepeng functioned as a tool for trading transactions transformed into a means of transactions in religious rituals. This research used the method of observation, literature study, and in-depth interviews to reveals the existence and role of uang kepeng or pis bolong in Bali. At present, uang kepeng has also become a craft commodity that has a role in tourism in Bali.